Management and ecology of river fisheries (Fishing News Books, 2000)
In this edited work, international experts in fisheries management and ecology review and appraise the status of river fisheries, assessment methodology, constraints on development, issues and options regarding management and associated problems in both temperate and tropical countries. Recommendations are made to improve management and an attempt is made to provide guidelines for formulating policy, for planning methodology and for evaluating future activities.